Leaching assessment of incineration bottom ash: laboratory and field-scale evaluations - Wei, Wei (Nanyang Technological University, 2025)
Waste-to-energy incineration significantly reduces the volume of municipal solid waste and has been widely adopted for global waste management. Incineration bottom ash is one of the primary residues from this process and has potential for recycling as construction materials, such as road bases, subbases, and concrete. However, the environmental leaching of hazardous substances, such as heavy metals, poses a significant challenge that limits its reuse. Therefore, treatment is essential for IBA to comply with relevant criteria before it can be safely repurposed. In Singapore, IBA treated by three commercial plants was utilized as road subbase material in a pilot road project. This study primarily focuses on the environmental leaching behavior of IBA, examined through various laboratory characterization and leaching tests, both in granular form and when embedded in concrete. By correlating these findings with real-site hydrogeological data, the study reveals the extent of heavy metal release and transport from IBA.